WORKSHEET ON INVERSE FUNCTIONS

Problem 1 :

Suppose f(x) = x2 - 1, with the domain of f being the set of positive numbers. 

(a) Evaluate f−1(8)

(b) Evaluate [f(8)]−1

Problem 2 :

Suppose f(x) = 4x + 6, evaluate f−1(5).

Problem 3 :

Suppose f(x) = 7x - 5, evaluate f−1(-3).

Problem 4 :

Suppose f(x) = 2 + (x - 5)/(x + 6), with the domain of f being the set of positive numbers. 

(a) Evaluate f −1(4)

(b) Evaluate [f(4)]−1

Problem 5 :

Suppose h(x) = 3x2 - 4, where the domain of h is the set of positive numbers, find h−1(x).

1. Answer :

(a) Evaluate f−1(8) :

f(x) = x2 - 1

Replace f(x) by y. 

y  =  x2 - 1

Interchange x and y. 

x = y2 - 1

Solve for y. 

x + 1 = y2

Taking square on both sides, 

y = ±√(x + 1)

Replace y by f-1(x). 

f−1(x) = ±√(x + 1)

f−1(8) = ±√(8 + 1)

±3

(b) Evaluate [f(8)]−1

[f(8)]-1 = 1/f(8)

= 1/(82 - 1)

= 1/(64 - 1)

= 1/63

2. Answer :

f(x) = 4x + 6

Replace f(x) by y. 

y = 4x + 6

Interchange x and y. 

x = 4y + 6

Solve for y. 

x - 6 = 4y

y = (x - 6)/4

Replace y by f-1(x).

f-1(x) = (x - 6)/4

f−1(5) = (5 - 6)/4

= -1/4

3. Answer : 

f(x) = 7x - 5

Replace f(x) by y. 

y = 7x - 5

Interchange x and y. 

x = 7y - 5

Solve for y. 

x + 5 = 7y

y = (x + 5)/7

Replace y by f-1(x).

f-1(x) = (x + 5)/7

f−1(-3) = (-3 + 5)/7

= 2/7

4. Answer :

f(x) = 2 + (x - 5)/(x + 6)

f(x) = [2(x + 6) + (x - 5)]/(x + 6)

f(x) = [2x + 12 + x - 5]/(x + 6)

f(x) = [3x + 7]/(x + 6)

f(x) = (3x + 7)/(x + 6)

(a) Evaluate f −1(4) :

f(x) = (3x + 7)/(x + 6)

Replace f(x) by y. 

y = (3x + 7)/(x + 6)

Interchange x and y. 

x = (3y + 7)/(y + 6)

Solve for y. 

x(y + 6) = 3y + 7

xy + 6x = 3y + 7

xy - 3y = 7 - 6x

y(x - 3) = 7 - 6x

y = (7 - 6x)/(x - 3)

Replace y by f-1(x).

f-1(x) = (7 - 6x)/(x - 3)

f−1(4) = (7 - 24)/(4 - 3)

= -17/1

= -17

(b) Evaluate [f(4)]−1.

[f(x)]−1 = 1/f(x)

[f(x)]−1 = (x + 6)/(3x + 7)

[f(4)]−1 = (4 + 6)/(12 + 7)

= 10/19

5. Answer :

h(x) = 3x2 - 4

Replace h(x) by y. 

y = 3x2 - 4

Interchange x and y. 

x = 3y2 - 4

Solve for y.  

x + 4 = 3y2

(x + 4)/3 = y2

Taking square on both sides, 

y = ±√[(x + 4)/3]

Replace y by h-1(x). 

h−1(x) = ±√[(x + 4)/3]

Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Trigonometry Word Problems Worksheet with Answers

    Jan 17, 22 10:45 AM

    Trigonometry Word Problems Worksheet with Answers

    Read More

  2. Trigonometry Word Problems with Solutions

    Jan 17, 22 10:41 AM

    Trigonometry Word Problems with Solutions

    Read More

  3. Writing Numbers in Words Worksheet

    Jan 16, 22 11:56 PM

    Writing Numbers in Words Worksheet

    Read More